HUBUNGAN SIKAP KEPALA KELUARGA TENTANG PENCEGAHAN DEMAM BERDARAH DENGUE BERDARAH DENGUE DI DUSUN MIRI DESA SRIHARJO KECAMATAN IMOGIRI KABUPATEN BANTUL - Lesmana, Tedy Candra; Antara, Antok Nurwidi; Ulu, Candra Armanda (Jurnal Kesehatan Masyarakat, 2016)
ABSTRACT Dengue Hemorrhagic Fever in Bantul often happens. One factor is a lack of attitude of families (KK) and behaviors in prevention of Dengue like Mosquito eradication nest with draining, closing and burying. This study aimed to determine the attitude of the head of the family relationships on prevention of Dengue Hemorrhagic Fever with behavior prevent Dengue Hemorrhagic Fever in the hamlet Miri, Sriharjo Imogiri, Bantul. The population of this study were 285 households with a sample of 74 people. Data were collected by questionnaire. Data analysis was performed using Spearman Rank with error level of 5%. Based on the results of the study single variable analysis showed a good attitude in the category KK sebanyak14,86%, category quite as much as 20.27% and less category as much as 64.86% and Behavior prevent Dengue Fever both categories as much as 13.51%, the category of pretty much 31 , 08% and less category as much as 55.41%. Results of the analysis of two variables with p value of 0.000 (0.000